2015
DOI: 10.1002/mds.26152
|View full text |Cite
|
Sign up to set email alerts
|

Statins, plasma cholesterol, and risk of Parkinson's disease: A prospective study

Abstract: Background Previous findings on the association of statins, plasma lipids, and Parkinson’s disease are confounded by the fact that statins also affect lipid profiles. We prospectively examined plasma lipids and statin use in relation to Parkinson’s disease in the Atherosclerosis Risk in Communities (ARIC) Study. Methods Statin use and plasma lipids were assessed at baseline (Visit 1, 1987–89) and at three triennial visits thereafter (Visits 2–4) until 1998. Potential Parkinson’s cases were identified from mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
137
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(155 citation statements)
references
References 29 publications
12
137
3
3
Order By: Relevance
“…Based on the present results, high serum lipid levels may have a beneficial effect on improving the monoaminergic neuron integrity and thus slowing PD progression. In addition, the present findings suggest that lowering plasma cholesterol with statins should be considered cautiously in PD patients, as has been indicated by Huang et al [17]. Their study showed that statin usage was associated with higher risk of PD after accounting for serum LDL-cholesterol levels, which is inconsistent with the hypothesis that statins might be neuroprotective for PD [40].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Based on the present results, high serum lipid levels may have a beneficial effect on improving the monoaminergic neuron integrity and thus slowing PD progression. In addition, the present findings suggest that lowering plasma cholesterol with statins should be considered cautiously in PD patients, as has been indicated by Huang et al [17]. Their study showed that statin usage was associated with higher risk of PD after accounting for serum LDL-cholesterol levels, which is inconsistent with the hypothesis that statins might be neuroprotective for PD [40].…”
Section: Discussioncontrasting
confidence: 56%
“…Although the findings are still controversial, the overall evidence favors an association between higher total cholesterol and lower PD risk [13,17]. Recent reports revealed a direct relationship between higher cholesterol levels and a slowing in the rate of decline in Parkinson's disease patients [18].…”
Section: Plasma Lipid Indicator Evaluationmentioning
confidence: 98%
“…The year of publication ranged from 2007 to 2016, thus spanning 10 years. Six studies were case-control design studies [8, 9, 14, 19, 22, 26], and 7 were cohort studies [17, 18, 20-24]. Eleven studies reported that the age of onset for PD development was over 65 years but 2 studies reported an age of onset below 60 years.…”
Section: Resultsmentioning
confidence: 99%
“…Of the included studies, 6were from North America [14, 18-20, 22, 26] 4 were from Europe [8, 9, 17, 24], and 3 were from Asia [21, 23, 25]. The year of publication ranged from 2007 to 2016, thus spanning 10 years.…”
Section: Resultsmentioning
confidence: 99%
“…Instructively, the commercially available statins (e.g., atorvastatin and simvastatin), which lower cholesterol levels by inhibition of 3-hydroxy-3-methylglutaryl coenzyme A reductase, have been implicated in neuroprotection against PD, AD, traumatic brain injury, and secondary progressive multiple sclerosis (Kumar et al, 2012;Malkki, 2014). In some instances, neuroprotection has been associated with the lipophilicity of the drug (Haag et al, 2009;Huang et al, 2015), but direct mitochondrial protection is not established either experimentally or clinically, and the well-known adverse effects of statins on mitochondria, such as inhibition of Coenzyme Q synthesis, is an important caveat with these agents (Golomb and Evans, 2008). The 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors cause a myopathy that has been attributed in part to a reduction in CoQ 10 levels (Potgieter et al, 2013).…”
Section: Mitochondrial Dysfunction Caused By Therapeutic Agentsmentioning
confidence: 99%